PENGARUH PERBEDAAN TEMPORER ANTARA LABA AKUNTANSI DENGAN LABA KENA PAJAK TERHADAP PERTUMBUHAN LABA KE DEPAN (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2013-2016) - Indah Rosida; Mohammad Amin; Junaidi Junaidi (Universitas Islam Malang, 2018)
ABSTRACTThis research was conducted with the aim to know the effect simultaneously and partially between accounting profit with taxable profit differences and Taxable to earnings growth in the future of manufacturing company in Indonesia.The population used in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the year 2013-2016. Sample selection using purposive sampling. Based on the criteria, obtained 40 manufacturing companies who become samples in this study. The method used in this study using multiple linear regression method.Based on the results of the analysis can be put forward several conclusions as follows: 1) Simultaneously accounting earnings have a significant positive effect on deposits of profit growth in the future. 2) Partially Deductible temporary differences have a significant positive effect on profit growth in the future. 3) Partially Taxable temporary differences have a significant positive effect on future earnings growth deposits.Keywords: Accounting Profit, Taxable Profit,Future Gain Growth